2017
DOI: 10.1016/j.ijhydene.2016.11.051
|View full text |Cite
|
Sign up to set email alerts
|

How the BoP configuration affects the performance in an air-cooled polymer electrolyte fuel cell. Keys to design the best configuration

Abstract: Air Cooled Polymer Electrolyte fuel cells (AC-PEFC) are recently receiving especial attention because they offer the possibility to integrate the oxidant and cooling subsystems in just one. This feature reduces not only the fuel cell weight, volume and cost but also the control complexity. In these fuel cells, the Oxidant/Cooling subsystem along with three others (Fuel, Electrical and Control) make up the Balance of Plant (BoP), which together with the stack comprise the full fuel cell. It is common to find wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However, these BoP components are costly and consume additional power which falls under the auxiliary losses of the system. 2 The total cost includes the capital cost for installing such BoP components and the associated operational and maintenance costs. The BoP components constitute nearly 35% of the total cost of the system for transportation applications.…”
Section: CCLmentioning
confidence: 99%
“…However, these BoP components are costly and consume additional power which falls under the auxiliary losses of the system. 2 The total cost includes the capital cost for installing such BoP components and the associated operational and maintenance costs. The BoP components constitute nearly 35% of the total cost of the system for transportation applications.…”
Section: CCLmentioning
confidence: 99%
“…In this section it is provided a solution for the implementation of the BoP, within the specifications of safety and performance. With hydrogen technologies, it is important to carry out a study of the equipment in subsystems that capture in the BoP, which has been shown to be essential to achieve a reliable design with optimal production [18].…”
Section: Balance Of Plant Of a Pem Electrolyzermentioning
confidence: 99%
“…Then, according to operation description, it can be deduced that in PEM electrolysis it is very important to ensure specific water conditions as well as safe hydrogen production conditions. Therefore, the correct design of the BoP is crucial to achieve a reliable implementation and an optimal electrolyzer operation [24].…”
Section: O 2 Separatormentioning
confidence: 99%